The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0034-72992004000300016
|View full text |Cite
|
Sign up to set email alerts
|

Disacusia sensorioneural autoimune em criança: relato de caso

Abstract: A disacusia sensorioneural autoimune é reconhecida como uma das poucas causas reversíveis de perda auditiva sensorioneural. Acomete na grande maioria das vezes mulheres entre 30 e 40 anos, sendo extremamente raro em crianças. O diagnóstico baseia-se no quadro clínico, testes laboratoriais, bem como resposta satisfatória a corticoterapia. O exame audiológico não apresenta características típicas. Neste trabalho os autores descrevem o caso de um menino de sete anos com diagnóstico de disacusia sensorioneural aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The renal toxicity observed in this present study is related to nephrotoxic and/ or vesical toxic effect of the drug, as reported by Costa et al (2004). According to Antunes & Bianchi (2004), the nephrotoxicity is one of the main side-effects of therapy with cisplatin, an antineoplastic drug as well as cyclophosphamide.…”
Section: Discussionsupporting
confidence: 73%
“…The renal toxicity observed in this present study is related to nephrotoxic and/ or vesical toxic effect of the drug, as reported by Costa et al (2004). According to Antunes & Bianchi (2004), the nephrotoxicity is one of the main side-effects of therapy with cisplatin, an antineoplastic drug as well as cyclophosphamide.…”
Section: Discussionsupporting
confidence: 73%